The chocolate castle clue [large type] : a chocoholic mystery - Carl, JoAnna (Carl, JoAnna. Chocoholic mystery., 2012)
Lee McKinney Woodyard discovers a dusty trophy inside TenHuis Chocolade that belongs to her aunt Nettie and her old high-school singing group, the Pier-O-Ettes. It's a trophy that brings back terrible memories of an unsolved murder years ago. Before Lee takes aim at the past, someone is murdered in the here and now. Lee needs to keep her eyes on the prize, hoping the trophy is a clue to finding the killer - before she's a target herself.